Adaptasi Masyarakat Dalam Menghadapi Bencana Banjir Di Sempadan Cisadane Kelurahan Paledang Bogor Tengah Kota Bogor - Bukhori Brata Kusuma; Muhammad Zid; Rayuna Handawati (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2020)
The purpose of this research is to know the only people who are in flood disaster area. This research is conducted in the boundary area Cisadane Village Paledang Bogor Central Bogor. Based on the analysis of the data conducted, the affected community does its sole by using their knowledge that is very minimal information and minimal knowledge related to disaster. However, the affected community can do its sole from the experience they experienced while living there, ranging from Mauri signs of flood disaster from natural condition, Course or from objects that exist around their house, as The power pole, and the house's retreat.